Grammatical mistakes of Albanian students in learning English as a foreign language - Spahiu, Isa; Kryeziu, Naim (Linguistics and Culture Review, 2021)
Making mistakes is an unavoidable element of learning and teaching a foreign language. Because there are virtually always exceptions to the "rules," English can be tough to master. This study focuses on the most prevalent grammatical errors made by Albanian students during the EFL (English as a foreign language) learning process, as well as the sources of these errors, in order to consider them while teaching English grammar. The purpose of this study is to find out to what extent Albanian EFL students to be successful in the use of prepositions, and how much impact their mother tongue has on their errors. Being aware of such mistakes in teaching and learning English grammar for communicative purpose may help the teacher in choosing the right teaching option that would pose fewer difficulties and problems to their learners and therefore, enhance students learning of English grammar. In this study, the terms error and mistake are used interchangeably to refer to the generation of incorrect forms in learners’ linguistic output. It has been highlighted that the effect of the learners’ native language is responsible for many of the errors.